Parametric design and IR signature study of exhaust plume from elliptical-shaped exhaust nozzles of a low flying UAV using CFD approach - Haq, Fazal; Huang, Jun (Results in engineering, 2022)
This paper describes the design, parametric study, and IR signature analysis of plume of a slit-shaped exhaust nozzle. Circular-shaped exhaust nozzles are generally used to get the essential thrust necessary for an aircraft flight. However, the Infrared (IR) signature of the exhaust plume emanating from these nozzles is very high, and the IR missile can easily lock and hit the aircraft. In this paper, the compressible flow CFD model using a realizable k-ε turbulence model is used to study the flow characteristics of the exhaust nozzle with different aspect ratios. The exit cross-section of the nozzle is kept elliptical up to a maximum aspect ratio of 10. IR signature for each nozzle shaped is calculated using a set of input parameters in Mid-wave IR and Long-wave IR spectral bands. The IR signature of exhaust plume in Long-wave IR spectral band is not significant due to high transmittance of species in the exhaust plume mixture. However, for this particular case of low flying UAV, a considerable reduction in the IR signature is recorded for the high aspect ratio nozzle in MWIR spectral band. •Slit-shaped exhaust nozzle reduce the length of the exhaust plume core.•Thermal signature of the nozzle exit plane is more prominent in MWIR spectral band.•Rapid decrease in the temperature shift the peak of radiant emission to larger wavelength band.